Herbivore, parasitoid and hyperparasitoid insects associated with fruits and seeds of Enterolobium contortisiliquum (Vell.) Morong (Fabaceae) - T. Morales-Silva; L. F. Maia; A. L. Martins; S. L. Modesto-Zampieron (Brazilian Journal of Biology, 2018)
Abstract This study aimed to inventory the herbivore insects associated with Enterolobium contortisiliquum (Vell.) Morong (Fabaceae) fruits and seeds and their primary and secondary parasitoids. Six samples collected between May and October 2013 yielded 210 fruits, from which 326 insects of six orders emerged: Coleoptera, Hymenoptera, Lepidoptera, Diptera, Thysanoptera and Psocoptera. Coleoptera (five families) was represented by the seed consumers Merobruchus bicoloripes Pic, Stator sp. Bridwell (Chrysomelidae, Bruchinae), two species of Silvanidae, one species of Scolytinae (Curculionidae), one species of Nitidulidae and one species of Cerambycidae. The cerambycid was also observed forming galleries on fruit mesocarp. Immature individuals of Lepidoptera were observed consuming the fruits and seeds. From the seven Hymenoptera families, only two species were associated with Coleoptera, being Horismenus Walker sp. (Eulophidae) as parasitoid of M. bicoloripes, and Neoheterospilus falcatus (Marsh) (Braconidae) as parasitoid of Scolytinae. The Lepidoptera parasitoids represented four genera: Pseudophanerotoma Zetel, Chelonus Panzer (Braconidae), Orgilus Nees (Braconidae) and Goniozus Forster (Bethylidae). The host associations for the reared parasitoids Bracon Fabricius (Braconidae), Pimplinae sp. (Ichneumonidae) and Perilampus Forster (Perilampidae) were not confirmed. We obtained a single representative of Diptera (Tachinidae) associated with Lepidoptera hosts in this food web.